2011
DOI: 10.1017/s146114571100099x
|View full text |Cite
|
Sign up to set email alerts
|

Val/Val genotype of brain-derived neurotrophic factor (BDNF) Val66Met polymorphism is associated with a better response to OROS-MPH in Korean ADHD children

Abstract: Research on psychostimulants, analysis of animal models and genetic association studies all suggest that the brain-derived neurotrophic factor gene (BDNF) may be a good candidate for pharmacogenetic studies of attention deficit hyperactivity disorder (ADHD). Yet to date there have been no pharmacogenetic studies of BDNF in ADHD. A total of 102 drug-naive ADHD children (8.7±2.1 yr) were treated with osmotic release oral system-methylphenidate (OROS-MPH) for 12 wk, and four kinds of response criteria were applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 70 publications
0
11
1
1
Order By: Relevance
“…Val allele homozygous were more frequently (81%) assessed as “not ill” or “very mild” according to CGI‐I compared to 37% of Met allele carriers ( P = 0.0002). Moreover, more than 50% reduction in ADHD‐RS scores was observed in 95.2% of the Val allele homozygous patients and in 74.1% of Met allele carriers ( P = 0.018) [Kim et al, ]. The Val/Val genotype has been related to increased activity‐dependent secretion of BDNF [Flanagin et al, ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Val allele homozygous were more frequently (81%) assessed as “not ill” or “very mild” according to CGI‐I compared to 37% of Met allele carriers ( P = 0.0002). Moreover, more than 50% reduction in ADHD‐RS scores was observed in 95.2% of the Val allele homozygous patients and in 74.1% of Met allele carriers ( P = 0.018) [Kim et al, ]. The Val/Val genotype has been related to increased activity‐dependent secretion of BDNF [Flanagin et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Met allele carriers show decreased volume in the dorsolateral prefrontal cortex and subcortical regions [Pezawas et al, ]. An explanation for better MPH response in ADHD children who are Val/Val homozygous might be due to a lower degree of brain anatomical deficit and functional impairment in these individuals [Kim et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Several candidate genotypic variants have been identified as associated with positive MPH response. For instance, (i) specific polymorphisms in the gene expressing synaptosomal associated protein of 25 kDa (SNAP‐25), a common gene candidate underlying ADHD, have been shown to correlate with the likelihood of MPH efficacy; (ii) also an allelic variant of SLC6A2 , which expresses the norepinephrine transporter, correlates with positive response to MPH; (iii) the Val 66 Met phenotypic variant of brain‐derived neurotrophic factor, a neuronal gene product that facilitates fiber connections and memory, has been predictive of MPH efficacy; (iv) specific indel allelic variants of the gene expressing the D4 dopamine receptor subtype, considered risk alleles for ADHD, have also been associated with an increased probability of MPH efficacy; (v) as have specific indel variants expressing the dopamine transporter (DAT) …”
Section: Gene‐by‐dose Effects and Emerging Precision Medicinementioning
confidence: 99%
“…Previously, the G allele of rs1800544 has been noted to be associated with the improvement of MPH response in children and adolescents (Cheon et al 2009 ; da Silva et al 2008 ; Polanczyk et al 2007 ). However, negative studies have also been reported in children and adolescents (Kim et al 2011 ; Park et al 2013 ) as well as in adults (Contini et al 2011 ). Interestingly, in our study of adult ADHD, the G allele was associated with MPH non-response.…”
Section: Discussionmentioning
confidence: 99%